Diplomasi Sains Komunitas Epistemik Jerman Dalam Meningkatkan Pembangunan Kolombia - Dzikiara Pesona Sadewa (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
This article discusses how the scientific diplomacy efforts undertaken by the German Epistemic Community in promoting Colombian development. The Epistemic Community is the liaison between the two countries in the hope of being able to contribute to a country's policy through science in dealing with various local and global issues and can also contribute to the development of Colombia. By using descriptive qualitative research methods along with the concept of epistemic community and scientific diplomacy, this study produced findings that the Science Diplomacy carried out by the German Epistemic Community in promoting development in Colombia manifested itself in the form of efforts to improve academic collaboration, support the implementation of academic activities within government agencies, and continue recommendations for the development of various aspects of science in the research sector related to development policy.